A (trans)formação continuada como vetor de e para a inovação em contexto(s) de ensino da escrita - Motta, Caroline Gomes (Universidade do Vale do Rio dos Sinos, 2020)
From the theoretical basis on innovation in the context of Portuguese language teaching (SIGNORINI, 2007), teaching writing (KOCH; ELIAS, 2010, DOLZ; GAGNON; DEC NDIO, 2010), professional development (BRONCKART, 2013) and stages formative mediation processes (BRONCKART, 2006), the aim of this dissertation is to analyze if the process of continuing education, called “Mother Language Teaching and Genre Education Projects in the Final Grades of Elementary School”, promoted by the Postgraduate Program in Applied Linguistics of Unisinos, in partnership with the Education Municipal Office of Novo Hamburgo / RS, has been configured as a vector of and for innovation in the teaching writing in basic education. For this purpose, from a qualitative research approach (DÖRNYEI, 2007), based specifically on the framework of Sociodiscursive Interactionism (BRONCKART, 1999, 2006, 2013), the analysis of three specific formation moments was performed: (i) the accomplishment of an activity that sought to highlight the previous representations of the collaborating teachers of this research about classes focused on the teaching writing; (ii) their experiential livingness in an initial production activity proposed by working with genre education projects (PDG), under the principle of process homology (SCHÖN, 2000); and (iii) the return to teaching praxis, based on the planning of a PDG (GUIMARÃES; KERSCH, 2014) and, more specifically, workshops focused on writing production work. For this purpose, from a qualitative research approach (DÖRNYEI, 2007), based specifically on the framework of Sociodiscursive Interactionism (BRONCKART, 1999, 2006, 2013), the analysis of three specific formation moments was performed: (i) the accomplishment of an activity that sought to highlight the previous representations of the collaborating teachers of this research about classes focused on the teaching writing; (ii) their experiential livingness in an initial production activity proposed by working with genre education projects (PDG), under the principle of process homology (SCHÖN, 2000); and (iii) the return to teaching praxis, based on the planning of a PDG (GUIMARÃES; KERSCH, 2014) and, more specifically, workshops focused on writing production work. From linguistic-discursive categories related to textual architecture (BRONCKART, 1999), we analyzed: (i) the thematic content of the collaborative teachers' verbalizations and the textual progression of this content from the use of specific discourse types and mechanisms of connection textualization and nominal cohesion, seeking to identify clues about previous representations and possible moments of awareness about the teaching writing from the perspective of PDG; (ii) the thematic content of the workshops planned by them in relation to the focus (s) of the teaching writing. The results of this research suggest that: a) the planning of PDGs can contribute to writing teaching practices situated and consistent with a dialogical proposal of text production; b) the proposed continuing education is configured as a vector of and for innovation in relation to an interaction-focused teaching writing, because the collaborating teachers evidenced, in the planned PDG workshops, that they assumed a different attitude from what they apparently had when they entered in the formation process; c) the focus on a specific concept of writing teaching showed that other focuses and operations tend to be weakened, and it is necessary to resume them in the future formative mediation processes. Therefore, this research contributes to investigations in the field of Applied Linguistics that seeks to promote and analyze the professional development of teachers in continuing education processes.
Keywords: Formação continuada de professores; Inovação em contextos de ensino; Ensino da escrita; Projeto didático de gênero; Interacionismo sociodiscursivo; Continuing teacher education; Innovation in teaching contexts; Teaching writing; ACCNPQ::Lingüística, Letras e Artes::Lingüística